Sensitivity analysis of the temperature profile changing law in the production string of a high-pressure high-temperature gas well considering the coupling relation among the gas flow friction, gas properties, temperature, and pressure - Cao, Lihu; Sun, Jinsheng; Zhang, Bo; Lu, Nu; Xu, Yuqiang (Frontiers in Physics, 2022)
The temperature profile plays an important role in the well integrity, the flow assurance and the well test. Meanwhile, the impact of the engineering conditions should not be ignored in the calculation of the well temperature profile. Therefore, this paper established a model to analyze the changing law of the temperature profile inside the production string of high pressure high temperature gas well (HPHT gas well). The proposed model considers the flow friction caused by high production rate. Meanwhile, the gas properties variations are taken into account to increase the model accuracy, including the gas density, the flow velocity and the viscosity. The analysis indicates that the temperature in the production string decreases more and more quickly from the reservoir to the wellhead. The wellhead temperature changes more and more slowly with time. When the reservoir temperature is too low to maintain production, it is useful to regulate the production rate or inject the thermal insulating fluid into the annulus to avoid the block caused by the wax deposition or the hydrate deposition. Considering the sensitivity, feasibility and cost, it is recommended to change the well temperature profile by adjusting the production rate. If not applicable, the thermal conductivity can also be optimized to change the temperature profile.